1982
DOI: 10.1182/blood.v60.1.213.bloodjournal601213
|View full text |Cite
|
Sign up to set email alerts
|

The demarcation membrane system of the megakaryocyte: a misnomer?

Abstract: The concept that the demarcation membrane system delineates platelets within the cytoplasm of megakaryocytes has been examined. In short-term culture of mouse bone marrow, mature megakaryocytes extended long, attenuated processes that were found by electron microscopy to have a limited amount of invaginated membrane. When such megakaryocytes were exposed to microtubule depolymerizing agents, the attenuated processes retracted, became thicker, and an extensive demarcation membrane reappeared. It is suggested fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 0 publications
2
71
0
Order By: Relevance
“…Megakaryocytes in 4-8 hr or 48 hr samples of bone marrow provide no obvious morphologic clues as to why their progeny appear differently from megakaryocytes at these time points, and the mean platelet volume shifts rapidly, before changes occur in megakaryocyte ploidy distribution and cytoplasmic appearance. Therefore, it is probable that final platelet size and cytoplasmic composition are not predetermined in the megakaryocyte cytoplasm but rather in the mar-row sinusoids, at the time of platelet or proplatelet release, as has been proposed in the "flow" model, by Radley et al (Haller and Radley, 1983;Radley and Haller, 1982;Scurfield and Radley, 1981). If this model is correct, and constrictions develop along megakaryocyte processes in sinusoids, then perhaps a hormonal regulator such as thrombopoietin, which has been shown to produce an increase in mean platelet volume (Levin et al, 1982;Vannucchi et al, 19881, may influence the frequency and subsequent breakage of constrictions; greater than normal inter-constriction intervals would produce large-sized platelets under perturbed conditions of thrombopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Megakaryocytes in 4-8 hr or 48 hr samples of bone marrow provide no obvious morphologic clues as to why their progeny appear differently from megakaryocytes at these time points, and the mean platelet volume shifts rapidly, before changes occur in megakaryocyte ploidy distribution and cytoplasmic appearance. Therefore, it is probable that final platelet size and cytoplasmic composition are not predetermined in the megakaryocyte cytoplasm but rather in the mar-row sinusoids, at the time of platelet or proplatelet release, as has been proposed in the "flow" model, by Radley et al (Haller and Radley, 1983;Radley and Haller, 1982;Scurfield and Radley, 1981). If this model is correct, and constrictions develop along megakaryocyte processes in sinusoids, then perhaps a hormonal regulator such as thrombopoietin, which has been shown to produce an increase in mean platelet volume (Levin et al, 1982;Vannucchi et al, 19881, may influence the frequency and subsequent breakage of constrictions; greater than normal inter-constriction intervals would produce large-sized platelets under perturbed conditions of thrombopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Matolcsy et al [13] studied the distribution of AgNORs in megakaryocytes from patients with myeloproliferative disorders and found that the AgNOR count in patients with chronic myelogenous leukaemia (in which ploidy is lower than normal) was significantly lower, and in polycythaemia vera and essential thrombocythaemia patients (in whom ploidy is higher than normal) was higher, than in healthy individuals, suggesting that protein synthesis increases with ploidy. Some experiments have been performed in cultured megakaryocytes and have shown that the disruption of microtubules by colchicine, nocodazole or vincristine results in the inability of the cells to form cytoplasmic processes or to undergo fragmentation for proplatelet formation, suggesting a microtubule basis for platelet extension [23][24][25][26][27][28][29]. Furthermore, the action of tubulin inhibitors by tubulin-depolymerizing agents (colcemid, colchicine or nocodazole) as well as stabilizing agents (taxol) has been shown to block cytoplasmic division without stopping DNA synthesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…The outlined 'platelet territories' inside the MKs of the propositus are different from the circulating platelets for they do not contain electron lucent vacuoles or membrane complexes. The proplatelet chains also have a limited amount of electron lucent vacuoles (Radley & Haller, 1982). It may be assumed that, following release from MKs, the spheroid shape of the platelets of the propositus is realized by invagination of the irregular boundary of the platelet territories.…”
Section: Discussionmentioning
confidence: 99%
“…This results in an elaborate invaginated membrane system, which may form a membrane complex, when it comes in contact with elements of the dense tubular system. Invagination of the boundary of putative platelets in the chains of proplatelets has also been proposed to explain the origin of the invaginated membrane system in discoid platelets (Radley & Haller. 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation